Implementation of Community Policing as an Effort to Increase Public Trust in the Police - Samuel hasian Hutabarat; Zainal Abidin pakpahan; Muhammad Yusuf Siregar (International Journal of Science and Environment (IJSE), 2026)
Public trust is the primary foundation for effective law enforcement. The Indonesian National Police (Polri), as a law enforcement institution, is required not only to suppress crime but also to build harmonious relationships with the community. This article analyzes the implementation of the Community Policing concept as a strategy to increase public trust in the Polri. Through a qualitative approach and literature review, this research finds that Community Policing, which emphasizes partnerships, problem-solving, and organizational transformation, is able to bridge the gap between the police and the community. Its implementation through programs such as Bhabinkamtibmas (Community Police), Child-Friendly Police (Police), and dialogic patrols has been proven to increase positive public perception. However, challenges such as organizational culture, limited resources, and internal resistance still need to be addressed to optimize the program. This article concludes that Community Policing is not just a program, but a new paradigm in policing that can strengthen the legitimacy of the Polri in the eyes of the public.